Study of the stress intensity factors in the bulk of the material with synchrotron diffraction - López-Crespo, Pablo; Vázquez Peralta, Javier; Simpson, C; Moreno-Morales, María Belén; Buslaps, T; Withers, Philip J. (Engineering Integrity Society, 2017)
In this work we present the results of a hybrid experimental and analytical approach for estimating the stress intensity factor. It uses the elastic strains within the bulk obtained by synchrotron X-ray diffraction data. The stress intensity factor is calculated using a multi-point overdeterministic method where the number of experimental data points is higher than the number of unknowns describing the elastic field surrounding the crack-tip. The tool is tested on X-ray strain measurements collected on a bainitic steel. In contrast to surface techniques the approach provides insights into the crack tip mechanics deep within the sample.
Artículo de Proceedings de Congreso Internacional Fatigue2017
Keywords: Estrés (Fisiología); Stress intensity factor; Bainitic steel